PEMBUATAN MOTION GRAPHIC SEBAGAI MEDIA PROMOSI UNTUK PROYEK DATSUN SIGAP: PEMBUATAN MOTION GRAPHIC SEBAGAI MEDIA PROMOSI UNTUK PROYEK DATSUN SIGAP - Saputra, Agesta Budy (Puslitbang Kopertip Indonesia, 2018)
Datsun SIGAP is a after-sales service organized by Datsun Indonesia. Datsun SIGAP aims to improve the quality of service to customers of Datsun Indonesia especially in the field of after sales service or service. To maximize the function of Datsun SIGAP service in the future, it needs an interesting and informative media campaign about the explanation of service and its advantages. The purpose of this project is to produce an interesting and informative media campaign in order to be able to convey information about Datsun SIGAP in a complete and interesting, which is packaged in the form of motion graphics using Adobe After Effects application, Adobe Photoshop, and Adobe Illustrator.